Dependence of the Sheet Resistivity and Current Noise Behaviour of the Grain Size and Volume Fraction of Conducting Material in Thick-Film Resistors Experiments - F. Müller; M. Wolf (Active and Passive Electronic Components)
Experimental results concerning the dependence of the sheet resistivity and the noise coefficient on the grain size and the volume fraction, respectively, of the metallic-like component in Bi2Ru2O7-based thick-film resistors are presented. The results are compared with current models for the electrical conduction mechanism in these resistors.